Comparative analysis of models assessment effectiveness of staff development - Olena Chumachenko; Svitlana Philchak (Cхід, 2013)
In the article researches the existing methods of efficiency evaluation of the staff development - Kirkpatrick, Phillips, Tyler, CIPP, Scrivens, Berd, McGi. Was considered the methodology of the personnel assessment of personnel department in the conditions of employment center; grounded the economic effectiveness of the workers training with an allowance for ageing of knowledge. In the article show that for government institutions and other organizations which provide services the optimal model for assessment effectiveness is McGi's assessment. The best model for companies that manufacture products is the Phіllіp's effectiveness (ROI).